Gradient Approximation in Flexible Multibody Systems Using a Multigrid Approach. Issue 1 (17th December 2018) - Moghadasi, Ali; Held, Alexander; Seifried, Robert
Abstract: The approximation of gradients with a multigrid approach is presented in the framework of flexible multibody systems, in which the flexible bodies are modeled using finite element method. For the cases where the number of design variables are high, for example, in topology optimization where the density of each element is chosen as a design variable, the gradient computation becomes computationally infeasible. The proposed approximation, in which the gradients are computed simultaneously on a fine grid and a coarse grid, can significantly reduce the computation time without hindering the accuracy of the gradients.